САЎЫН СЫЙЫРЛАРДЫҢ СҮТИНЕ ТӘСИР КӨРСЕТИЎШИ СЫРТҚЫ ФАКТОРЛАР - Казакбаев, Б. (FAN va JAMIYAT, 2017)
The article deals with the issues of development of the branch of stock-breeding and increasing the product's quality in farming and personal subsidiary facilities. The author gives recommendations how to organize contents and feeding and deal with tribe work in cattle breeding.